DESAIN BAHAN AJAR LEMBAR AKTIVITAS TERSTRUKTUR UNTUK MENGOPTIMALKAN KEMAMPUAN PENALARAN DAN SELF-ESTEEM MATEMATIS MAHASISWA - Kus Andini Purbaningrum; Prahesti Tirta Safitri; Aan Subhan Pamungkas (Universitas Sultan Ageng Tirtayasa, 2020)
This study aims to develop instructional materials in the form of structured activity sheets to optimize mathematical reasoning and self-esteem abilities of Mathematics Education Study Program students at FKIP Muhammadiyah University, Tangerang (UMT). The development of teaching materials is carried out through the stages of the analysis of learning prerequisites, designing teaching materials, testing by experts and users and field testing. Data collection instruments use questionnaires and questions to measure students' mathematical reasoning and self-esteem abilities, which are given at the end of all learning. The research results obtained criteria above 60%, there are 22 students (81.48%) have good reasoning ability and 23 students (85.18%) have good mathematical self-esteem. This shows the teaching material in the form of activity sheets that are well structured and feasible to use. Keywords: Structured Activity Sheet, Reasoning, Self-Esteem